Technological Inclusion in Small Coffee Plantations in the South of the State of Minas Gerais, Brazil - Corsini, Wanêssa Tavares Campos; Corsini, Fábio dos Santos; Angelocci, Marina Ariente; Naves, Luciana de Paula; Paiva, Leandro Carlos; Silva, Adriano Bortolotti da; Goes, Bruno Cesar; Putti, Fernando Ferrari (Journal of Agricultural Studies, 2021)
World market is increasingly expanding in food production. Coffee has been underscored within the new scenario and positively impacts the economy of the country, together with other crop types. Current analysis assesses the insertion index of new technological resources and the fastness of the production process of coffee culture on small coffee plantations in the south of the state of Minas Gerais, Brazil. Field study comprised the analysis of 225 farms by an open and closed questionnaire. Data, analyzed by cluster analysis, revealed that small farms have invested in technologies and data access technology for harvest and production processing. Corroborating other scientific investigations, the above activity decreased the labor force and consequently triggered an increase in profits for small producers.